Nominal Exchange Rate Dynamics in the European Monetary System - Michael G. Spencer (Queen's University, Department of Economics, 1990)
The EMS is modeled as imposing dual reflecting barriers on the exchange rate process. This policy leads to a state-dependent conditional variance for exchange rate changes. This variance is always less than that under a pure free float regime. A method of Simulated Moments procedure is employed to estimate the parameters of the model. Simulations with the estimated parameter values show that the model predicts non-normality and non-stationarity in the distribution of exchange rate changes and that these characteristics diminish with aggregation.
Keywords: 211; 431; 330; Browian motion; target zones; leptokurtosis; ARCH; Method of Simulated Moments